Pendekatan Story Telling Dalam Pembelajaran Dokkai: Penelitian Terhadap Mahasiswa Jurusan Pendidikan Bahasa Jepang - Juangsih, Juju (Lingua Cultura, 2012)
The research was conducted in accordance with the phenomenon occurred in Dokkai learning in which the students show lack understanding on reading. The aims of the research are: (1) to obtain clear description of the findings comprehensively about the reality in Dokkai learning of the students of JPBJ FPBS UPI as the learning goals through the story telling approach; (2) to figure out the difficulties and factors influencing the low level of understanding Japanese reading (Dokkai). The population of the research is the third semester students of Japanese Education Department FPBS UPI Bandung as 19 students taken randomly from Chuukyuu Dokkai I course. Qualitative method is employed using quasi experimental design. Thus, in the research, there is no control group as the comparing class. From the result of data analysis, we find that (1) according to the questionnaire result, 90% of the respondents respond that the story telling approach in Dokkai course is interesting; (2) the students must be able to comprehend the reading text and then retell it; (3) the class becomes more active and effective.